AUDIT ENERGI UNTUK PEMAKAIAN LISTRIK DI INDUSTRI - Setiono, Iman (Proceeding SENDI_U, 2015)
One important integral part of the production process in the industry is the provision of infrastructure facilities,one of which is the provision of electricity. The availability of electric power in most industries are relying onsupply of electricity, although there are also some others have their own power generators, good only used forpeak load or for emergencies, where the supply of electricity from PLN was having blackouts.The problems that arise in every use of electricity, both of which use the supply of electricity from PLN as wellas those of his own generation is efficiency. Definition of efficiency is the ratio between the costs incurred by theresults obtained. At every company must always stressed the importance of efficient, including in terms ofelectrical power consumption.Menurut guidelines for the implementation and monitoring of energy conversionin the Ministry of National Education, Energy Consumption Intensity values obtained (IKE) that electricityconsumption amounted to 4.17 up to 7.92 KWh / m2 / month very efficient Meanwhile, when power consumptionreaches 23.75 up to 37.5 KWh / m2 / month including a very wasteful.To achieve a high level of efficiency, somethings can be done, such as by replacing the electrical appliances are wasteful use of electricity, installingcapacitors at the load circuit, and perform load management usage settings.Keywords: efficiency, electric power, industry